Hokusai beyond the great wave - Katsushika, Hokusai 1760-1849 (2017)
Hokusai created sublime works during the last thirty years of his life, right up to his death at the age of ninety. Publications have hitherto presented his long career as a chronological sequence. This book takes a fresh approach based on innovative scholarship: thematic groupings of works are related to the major spiritual and artistic quests of Hokusai's life. Hokusai's personal beliefs are studied here through major brush paintings, drawings, woodblock prints and illustrated books. The book gives due attention to the contribution of Hokusai's daughter Eijo (Oi), an accomplished artist in her own right. Hokusai continually explored the mutability and minutiae of natural phenomena in his art. His late subjects and styles were based on a mastery of eclectic Japanese, Chinese and European techniques and an encyclopaedic knowledge of nature, myth, and history. Mount Fuji was the most significant model for Hokusai in his quest for immortality. This collection of Hokusai's works draws on the finest to be found in Japan and around the world, making this the most important publication for years on Hokusai, and a uniquely valuable overview of the artist's late career.